A. Developper 1x(b+c) .(-1)x(b+c)
b. Recopier et completez : a+(b+c)=a+(-1)x(b+c)=a+(-...)+(-...)=...
c. Recopier et completer : a-(b+c)=a+(-1)x(b+c)=a+(-...)+(-...)=...
d . Reduire chacune des expressions suivantes :
2x+(3x+4) -5x+(3x-4) 3x(2x+6) -x-(-9x+1)

1
tu es sur de tes enoncés b et c?
oui

Réponses

2013-12-04T21:55:54+01:00
A. Developper  
1x(b+c)
=b+c

(-1)x(b+c)
=-b-c

b. Recopier et completez :
a+(b+c)=a+1x(b+c)=a+b+c

c. Recopier et completer : a-(b+c)=a+(-1)x(b+c)=a+(-b)+(-c)=a-b-c

d . Reduire chacune des expressions suivantes :
2x+(3x+4)
=2x+3x+4
=5x+4

-5x+(3x-4)
=-5x+3x-4
=-2x-4

3x(2x+6)
=6x²+18x

-x-(-9x+1)
=-x+9x-1
=8x-1